A Two-Level Factorial Design for Screening Factors that Influence the Growth of Pseudomonas sp. Strain Dry135 on Acrylamide - Rahman, M.F.A.; Khayat, Mohd Ezuan; Abubakar, Aisami; Yakasai, Hafeez Muhammad; Shukor, Mohd Yunus (Journal of Environmental Microbiology and Toxicology, 2022)
Polyacrylamide is one of the most important sources of acrylamide in soil because it degrades into acrylamide over time. The breakdown of acrylamide by bacteria has experienced a steady but consistent increase in interest all over the world as a bioremediation technique. In this investigation, a previously obtained molybdenum-reducing bacterium with amide-degrading capabilities was found on critical parameters leading to optimum growth on acrylamide utilizing a two-level factorial design. The two-level factorial design was used in the screening of five independent parameters impacting the bacterium’s growth on acrylamide. These variables include pH, temperature, incubation period, acrylamide concentration, and ammonium sulphate concentration. The two-factor factorial design was successful in identifying major contributing parameters in the growth of this bacterium on acrylamide, which were acrylamide concentration, pH, and incubation time (p<0.05), which can be further optimized using RSM in future research. ANOVA, Pareto’s chart, pertubation’s plot, and other diagnostic plots were used to analyze the significant contributing components or parameters. Diagnostic plots such as half-normal, Cook’s distance, residual vs runs, leverage vs runs, Box-Cox, DFFITS, and DFBETAS all supported the two-level factorial result. The acrylamide range used in this study was well within the range reported to being tolerated by the majority of acrylamide-degrading bacteria. Incubation time is an expected finding because longer incubation time allows for higher growth, and incubation time ranging from two to five days for optimized growth has been documented in numerous acrylamide-degrading bacteria. Most acrylamide-degrading microorganisms grow well in near-neutral environments, and the results obtained in this investigation are consistent with published literature trends.